Structure and transcription of the allantoate permease gene (DAL5) from Saccharomyces cerevisiae. - Rai, R (1988)
We determined the nucleotide sequence of the DAL5 gene, which encodes a component of the allantoate transport system. Translation of the sequence revealed that the DAL5 gene product is highly hydrophobic. It possesses an alternating motif of hydrophilic sequences that can potentially be folded into alpha-helices and hydrophobic sequences that can potentially be folded into beta-pleated sheets. These are expected characteristics of an integral membrane protein, which correlate well with DAL5 gene function. S1 protection fragments generated by DAL5 transcripts exhibited high heterogeneity over a 30-base-pair range. This pattern of fragments was not affected by growth conditions of the cells or the conditions of the assay.